IoT-Based Vehicle Monitoring System on LoRa Network: Addressing Community Needs in Indonesia - Zulkifli, Fitri Yuli; Halimsurya, Ervin; Ayyasy, Muhammad; Luthfi, Fitya; Alinursafa, Ibnu (International Journal of Electrical, Computer, and Biomedical Engineering, 2024)
Our innovative IoT-based vehicle monitoring system emerges from a comprehensive survey among vehicle owners. The device circuit is designed using ESP32, GPS to detect location and speed, MPU6050 to detect vibrations from the vehicle engine, and a relay that is used to disconnect the vehicle socket if needed. The data collected from each component is sent through the LoRa Antares network. Access to the data can be done using a cell phone through the MOTRAV application that has been integrated with the Antares server. The designed system is able to display the location, speed, and condition of the vehicle consistently with an average delay of 7 seconds and can receive 65% of the control signals to start and stop the vehicle engine. The system can also send a warning notification if the vehicle that is not being used is detected at a speed of more than 5.5 km/h with engine vibrations detected reaching 28 vibrations/5 seconds.